PENDEKATAN BEHAVIOR TERHADAP EFIKASI DIRI - Nur Hasan (LP2M Universitas Ibrahimy, 2016)
The purpose of this study is to determine the correlation of behavior approach toward self-efficacy. Subjects of this study totaled 35 students. Data collected by behavior approach scale (operant conditioning) and self-efficacy scale. Analisis that used in this research is the statistical data analysis by the number of data pairs of product moment correlation. Based on the analysis turned out the value of r xy = 0.394. This number is greater than the significance level of 5% = 0.334 to N = 35. It means significant that the null hypothesis reads